Assessing young adults' menopause knowledge to increase understanding of symptoms and help improve quality of life for women going through menopause; a student survey - Vaishvi Patel; Sue Ross; Beate C. Sydora (BMC, 2023)
Abstract Background Due to menopause being a largely invisible and under-discussed topic in wider society, women often deal with menopause-related complications on their own. Social support and awareness have been shown to reduce negative menopausal experiences; however, lack of menopause knowledge, particularly among younger people, may deter support for women suffering from menopause symptoms. This study aims to assess the level of knowledge young adults have on menopause to be able to create interventions that target knowledge gaps and increase understanding of women's experiences and difficulties during their menopause transition. Methods We created an electronic questionnaire based on menopause literature and guidelines from Menopause Societies. It was pilot-tested on young people in the target group age (n = 14; 7 male and 7 female), menopause clinicians (n = 5), and women experiencing menopause (n = 4). The final survey included questions on participant demographics, general menopause knowledge, and options to support menopause management and was distributed through university student newsletters. Responses over a two week period were collected anonymously. Descriptive statistics were applied to characterize participants, define menopause knowledge, and identify gaps. Chi-squared statistics was used for group comparison, and open questions were analyzed using qualitative content analysis. Results Survey responses were collected from 828 students; the average age was 22.1 ± 5.1 and 83.6% were female. Participants belonged to all faculties and included students from a variety of family settings and living conditions. Knowledge questions revealed a good understanding of the basic menopause physiology for most respondents, but there were gaps in understanding of symptoms and symptom management. Female sex and personal connection to menopausal women had a positive effect on the degree of menopause knowledge. Both males and females reported increased knowledge confidence at the end of the survey. Conclusion Our survey provides evidence that young adults of both sexes have a general baseline knowledge of menopause and its symptoms and are open to learning strategies to help support menopausal women. Our findings will assist in developing targeted educational resources to increase social support and awareness, reduce stigma and improve the quality of life for menopausal women, and help prepare younger women for their future menopause journey.